Evaluation of variability among breeding lines and cultivars of taro (Colocasia esculenta) in Papua New Guinea using IáR fingerprinting and agro-morphological characterization - Okpul, T.=700 1 Mace, E.S.; Godwin, I.D.; Singh, D.; Wagih, M.E.
(Es,Fr,En)
ilus., 45 ref.
Keywords: COLOCASIA ESCULENTA; RECURSOS GENETICOS; ADN; MARCADORES GENETICOS; EVOLUCION; ITALIA; AGROMORFOLOGIA; MALANGA